Determination of Human Fibrinopeptide A by Radioimmunoassay in Purified Systems and in the Blood - Budzynski, A. Z; Marder, V. J (Thrombosis and Haemostasis, 1975)
The formation of fibrin clots or circulating soluble fibrin is accompanied by the appearance of fibrinopeptides. Measurement of the fibrinopeptide concentration in plasma can provide important information on the rate of conversion of fibrinogen to fibrin by thrombin. This rate varies under different physiologic and pathologic conditions. Fibrinopeptide A is a better molecular marker of the conversion than fibrinopeptide B since it is the first peptide to be cleaved by thrombin. A radioimmunoassay technique has been developed for the quantitative determination of human fibrinopeptide A. The procedure detects human fibrinopeptide A at a concentration of approximately 0.05 ng/ml. The fibrinopeptide A concentration in plasma of normal persons was found to be approximately 0.5 ng/ml. The variation of fibrinopeptide A content in normal persons may reflect its rapid formation and catabolism. A significantly increased concentration of this peptide was found in a patient during defibrination therapy with a purified enzyme from the venom of Agkistrodon rho-dostoma and in patients suffering from retinal vascular occlusions.